Bank Precautionary Principles Against Fraud In Ijarah Muntahiya Bit Tamlik Agreements - Jasmine Sarah Nabilla; Nur Chanifah; Letizia Dessy Andreassari (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The development of financing products in Islamic banking in Indonesia has encouraged the use of various contracts that comply with Sharia principles, including the Ijarah Muntahiya Bit Tamlik (IMBT) contract. IMBT combines a leasing mechanism (ijarah) with the transfer of asset ownership to the customer at the end of the contract period. This financing model is widely used because it provides flexibility for customers while remaining compliant with Islamic principles. However, the IMBT contract structure involves two stages of transactions leasing and ownership transfer which may create legal and operational complexities. If not implemented carefully, this structure may open opportunities for fraud and other risks in Islamic banking operations. This study aims to analyze the implementation of the prudential principle in the application of IMBT contracts in Islamic banking and to formulate regulatory strengthening to prevent potential fraud in IMBT financing practices. The research uses a normative juridical method with statutory and conceptual approaches. Legal materials consist of primary legal sources in the form of laws and regulations related to Islamic banking, secondary sources such as books, academic journals, and scientific publications, and tertiary sources including legal dictionaries and other supporting references. The analysis of legal materials is conducted using grammatical and systematic interpretation methods.The findings show that the prudential principle in Islamic banking has been normatively regulated in several legal frameworks. However, existing regulations remain general and do not specifically regulate operational parameters for implementing the prudential principle in IMBT contracts. This regulatory gap may create legal loopholes that increase the risk of fraud. Therefore, strengthening regulatory provisions is necessary by establishing clearer operational parameters for the implementation of prudential principles at each stage of IMBT financing. Such measures are important to ensure legal certainty, reduce fraud risks, and strengthen public trust in the Islamic banking system.